EFFECT OF FEEDING TOTAL MIXED RATION (TMR) ON BLOOD PROFILES IN LACTATING COWS* - S. SARMA2, NITUL SAIKIA ; B. N. SAIKIA1 (Indian Journal of Animal Production and Management, 2017)
Eighteen crossbred lactating cows were randomly selected for the experiment on thebasis of live weight and milk yield. The animals were divided into three groups and allottedto three dietary treatments, viz.- T0, T1 and T2. Animals in T0 groups were fed by conventionalmethod (concentrate and roughages fed separately) and feeding of animals in T1 and T2were done in the form of total mixed ration, where the roughage: concentrate ratio wasmaintained at 40:60 and 50:50, respectively. The feeding trial was conducted for 120 days.Blood samples were analyzed at monthly interval. The concentration of blood glucose, totalserum protein, BUN and serum creatinine did not differ significantly (P>0.05) among theexperimental groups. Thus, feeding system did not have any significant impact on theconstituents of blood.